State Fiscal Service as a body of public administration - Марущак, Анна Валеріївна; Марущак, А. В.; Марущак, Анна Валерьевна; Marushchak, Anna V. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article examines the scientific and legal characteristics of the State Fiscal Service of Ukraine and the theoretical and legal analysis of its functions and powers. It is proved that the State Fiscal Service is a body of public administration, which is carried out in the field of finance. The normative-legal acts regulating the activity of the State Fiscal Service are studied and the basic scientific concepts of its activity are considered. It is also proved that the powers of the SFS have a sign of discretion. It is substantiated that among the powers of the SFS can be distinguished control, expert-analytical, preventive, renewal. In turn, control powers can be classified depending on the scope of control: powers of tax control, budget, and customs control. The functions of the SFS include control, expert-analytical, prognostic, preventive and the function of fiscal administration.

У статті досліджено науково-правову характеристику Державної фіскальної служби України та теоретико-правовий аналіз її функцій і повноважень. Доведено, що Державна фіскальна служба є органом державного управління, який здійснюється у сфері фінансів. Досліджено нормативно-правові акти, що регулюють діяльність Державної фіскальної служби, та розглянуто основні наукові концепції її діяльності. Також доведено, що повноваження ДФС мають ознаку розсуду. Обґрунтовано, що серед повноважень ДФС можна виділити контрольні, експертно-аналітичні, превентивні, правопоновлюючі. У свою чергу контрольні повноваження можна класифікувати залежно від обсягу контролю: повноваження податкового контролю, бюджетного та митного контролю. До функцій ДФС належать контрольна, експертно-аналітична, прогностична, профілактична та функція фіскального адміністрування.
Marushak A. V. State Fiscal Service as a body of public administration / A. V. Marushak // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 249-264.
Keywords: State Fiscal Service of Ukraine; discretion; powers of the SFS; functions of the SFS; Державна фіскальна служба України; розсуд; повноваження ДФС; функції ДФС; Research Subject Categories::LAW/JURISPRUDENCE::Public law